Existence of a multiplicative basis for a finitely spaced module over an aggregate - Roiter, A. V.; Sergeychuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
It is proved that a finitely spaced module over k-category admits a multiplicative basis (such a module gives rise to a matrix problem in which the allowed column transformations are determined by a module structure, the row transformations are arbitrary, and the number of canonical matrices is finite).